Impact of scientist-farmer interface in rainfed agro-ecosystem of North West Himalayan region: A case of Farmer FIRST Project in Doon Valley - BIHARI, BANKEY; SINGH, MADAN; BISHNOI, RAJESH; ROY, TRISHA; SINGH, LAKHAN; KUMAR, SURESH; CHAND, LEKH; KADAM, D M; SHRIMALI, S S; MAURYA, U K; MURUGANANDAM, M; SHARMA, S K; et al. (The Indian Journal of Agricultural Sciences, 2020)
In North West Himalayan region, farmers tend to face problems related to production and natural resource management due to steep slopes; fragile geology and frequent landslides which leads to high soil erosion. The present study was conducted with the objective to assess the impact of Farmer FIRST Project on the livelihood of beneficiary farmers of study area. A sample of 300 farmers comprising of 180 beneficiary and 120 non-beneficiary farmers were selected through multi stage random sampling. To delineate the impact, with-without and before-after comparison on different aspects of Farmer FIRST Project were carried out. Study revealed that there exists a significant difference between beneficiary farmers and non-beneficiary farmers on various aspects, viz. awareness level, change in decision making behaviour, change in marketing behaviour, change in yield, change in income, change in cropping intensity and change in average annual employment days. Before-after comparison of beneficiary farmers showed that there is a significant increase in crop yield, cultivable area and average annual employment days. Hence, there is a need of upscaling the project for inclusion of more numbers of farmers and securing their livelihood.